(untitled) (Global Journal of Medical Research, 2021)
Introduction: EmONC is one of the interventions that reduce maternal and newborn morbidity and mortality by treatment of complications that may arise during pregnancy and childbirth. To support provision of EmONC service to critically ill patients, in 2018, Maternity WhatsApp Groups (MWGs) were established to render technical assistance to frontline skilled health care providers. Materials and methods : A total of 9 MWGs were formed with members from Regional and District Health Management Teams, hospitals (referral and district), health centres and HFs (both public and private). Clinicians, paramedics and policy makers constituted membership of groups. Interactive messages generated from groups were exported in notebook and then word. Generated were manually coded into themes and subthemes using the structural functionalism and grounded theories. An inductive approach was used to analyze data.